Impact of COVID-19 and border closures on North Korean markets: A comparison with international prices - Seungho Jung; Dawool Kim; Kyoochul Kim (Asia and the Global Economy)
This study examines the impact of COVID-19 and border closures on North Korean markets by comparing the prices of key goods—rice, gasoline, diesel, and exchange rates—with those in the Chinese and global markets. By analyzing market price data, we assess North Korea's economic connectivity to international markets, particularly through China, and how pandemic-induced disruptions affected this linkage. Empirical results reveal that North Korean market prices for these goods generally maintain a long-term equilibrium relationship with international and Chinese prices, although the COVID-19 period disrupted this relationship. These findings suggest that North Korea's macroeconomic stability, especially price levels, is influenced by external factors through its economic ties with China.